2010
DOI: 10.1007/s00774-010-0227-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the morpho-densitometric parameters of the lumbar pedicles in osteoporotic and control women undergoing routine abdominal MDCT examinations

Abstract: In transpedicular surgical operations, the pedicle should be safely penetrated. In this study, we hypothesize that morpho-densitometric data describing the physical status of the pedicle isthmus in osteoporotic versus control postmenopausal women may be generated using high-resolution three-dimensional images obtained from routine abdominal multidetector computed tomography (MDCT) scans. Thus, 32 osteoporotic and 38 postmenopausal control women had a routine abdominal scan using a 16-row CT scanner. Images of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…There are a few studies which have shown the possibility of using diagnostic CT images (with automated exposure control) for estimating bone mineral density [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies which have shown the possibility of using diagnostic CT images (with automated exposure control) for estimating bone mineral density [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is significant because it showed that HU measurements within a ROI very specific to spine surgery planning (ie, the pedicle isthmus) was consistent with osteoporosis status and fragility fracture. 66 …”
Section: Resultsmentioning
confidence: 99%
“…Мультиспиральная томография (МСКТ), магнитно-резонансная томография (МРТ) и сцинтиграфия скелета могут рассматриваться в качестве дополнительных методов дифференциальной диагностики [26][27][28][29].…”
Section: методы оценки переломов тел позвонковunclassified